Comparison of surgical efficacy between direct anterior approach and posterolateral approach in the treatment of sarcopenia with femoral neck fractures - Zhaoyang Yin; Qin Hu; Bin Zhang; Jin Yi; Hailong Zhang; Jian Yin (BMC Geriatrics, 2024)
Abstract Background Femoral neck fracture (FNF) is a prevalent injury among the elderly, associated with significant morbidity and mortality. Total joint arthroplasty (TJA) has markedly enhanced the quality of life for many patients; however, the benefits of the direct anterior approach (DAA), which has gained popularity in recent years, remain a subject of debate. Sarcopenia frequently occurs in patients with FNF and is linked to adverse surgical outcomes. This study aims to compare the effects of the DAA and the posterolateral approach (PLA) on the efficacy of TJA surgery in patients with FNF who also present with sarcopenia. Methods This study retrospectively analyzed the clinical data of patients with FNF who underwent total hip arthroplasty (THA) using either DAA or PLA from December 2019 to December 2022. A total of 141 individuals were included, comprising 52 in the DAA group and 89 in the PLA group. The cross-sectional area (cm²) of the musculature at the pedicle level of the 12th thoracic vertebra (T12) was measured using chest computed tomography (CT). The skeletal muscle index (SMI) was calculated by dividing the cross-sectional area of the muscle at the T12 pedicle level by the square of the individual’s height. Sarcopenia was diagnosed when both grip strength and SMI values fell below the diagnostic cutoff. The study compared various factors, including age, gender, SMI, body mass index (BMI), American Society of Anesthesiologists (ASA) classification, operation time, incision length, blood loss, blood transfusion, hemoglobin drop, albumin drop, postoperative time to ambulation, length of hospitalization, visual analogue scale (VAS) score, Harris score at one and six months post-surgery, complications, revision rate, one-year survival rate following surgery, and patient satisfaction. Results There were no statistically significant differences between the two groups regarding gender, age, SMI, BMI, ASA, operation time, blood transfusion, VAS score six months post-surgery, revision rate, satisfaction, and survival rate (P > 0.05). The incision length, blood loss, hemoglobin drop, albumin drop, hospitalization duration, VAS score, and complication rate one month after the operation in the DAA group were all significantly lower than those in the PLA group (P < 0.001). Additionally, the Harris scores at one month and six days post-operation were superior in the DAA group compared to the PLA group (P < 0.001). Furthermore, the incidence of complications in the DAA group was lower than that in the PLA group (P = 0.041). Univariate and multivariate Cox regression analyses indicated that age was an independent risk factor for patients’ mortality risk (95% CI: 1.064–1.479, P = 0.007). Conclusion DAA results in reduced surgical trauma, alleviates postoperative pain, decreases the incidence of complications, enhances the recovery of patients’ mobility functions, shortens hospital stays, and is particularly suitable for FNF patients with sarcopenia.